Immobilizing mobility: Border ethnography, illiberal democracy, and the politics of the "refugee crisis" in Hungary - KALLIUS, ANNASTIINA; MONTERESCU, DANIEL; RAJARAM, PREM KUMAR (American ethnologist, 2016)
ABSTRACT In the summer of 2015, more than 350,000 migrants moved through Hungarian territory. Almost immediately there emerged in response a dialectic between, on the one hand, depoliticizing narratives of crisis that sought to immobilize the migrants and, on the other, concrete political mobilization that sought to facilitate their mobility. While state institutions and humanitarian volunteer groups framed mobility in terms that emphasized a vertical form of politics, a horizontal counterpolitics arose by the summer's end, one that challenged hegemonic territorial politics. The state's efforts to immobilize resulted only in more radical forms of mobility. Outlining an ethnography of mobility, immobilization, and cross‐border activism, we follow the dramatic yet momentary presence, and subsequent absence, of migrants in an evanescent rebel city marked by novel political solidarities. [mobility, immobility, transit zones, border politics, refugees, migrants, Hungary]